6z+2z-4z+12=36

Simple and best practice solution for 6z+2z-4z+12=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6z+2z-4z+12=36 equation:


Simplifying
6z + 2z + -4z + 12 = 36

Reorder the terms:
12 + 6z + 2z + -4z = 36

Combine like terms: 6z + 2z = 8z
12 + 8z + -4z = 36

Combine like terms: 8z + -4z = 4z
12 + 4z = 36

Solving
12 + 4z = 36

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + 4z = 36 + -12

Combine like terms: 12 + -12 = 0
0 + 4z = 36 + -12
4z = 36 + -12

Combine like terms: 36 + -12 = 24
4z = 24

Divide each side by '4'.
z = 6

Simplifying
z = 6

See similar equations:

| 8+0.1Q=20-0.2Q | | (5x-20)+(5x-20)=180 | | f(x)=120x-.4x^4+800 | | 3x+8+-8= | | -5(v-3)=6 | | 5z+6=26 | | 10x+11x=126 | | 5x+6x-8x-20=4 | | -16x^2-108x+160=0 | | 11x+y=180 | | 3y+11+7x+4=180 | | f(x)=x^3-3x^2-9x+4 | | 20+7y=-6+15y | | (3x-14)+2x+25=180 | | (x-(2+2i))(x-(2-2i))(x+1)(x-2)= | | 26=-2y | | 8-5n=-2 | | 5x+6x-8x=24 | | 5.75x+3.5=9.25x | | (5x+9)(8x-15)=180 | | 4(w-5)=3(w+3) | | y=x^2+14x-32 | | 6+7(n-7)=-85 | | 4z+5=6z+10 | | 3=-2(x+2) | | 7(4n+5)=5(2n+7) | | y(y-3)+6=2y | | G-9.3=9.2 | | 4y-2y+18=12 | | 5n-8n+4= | | 6+7n-49=-85 | | 20m+12=30m-18 |

Equations solver categories